Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus Dan Dana Bagi Hasil Terhadap Belanja Pegawai (Studi Emipis Terhadap Kabupaten/Kota Di Provinsi Jawa Tengah Tahun 2013-2015) - Aini, Fitri Nur, Andy Dwi Bayu Bawono, SE., M.Si., Ph.D (2017)
The aim the research to examine the effect Local Revenue, General Allocation Fund, Special Allocation Fund and Revenue Local Revenue for Servent Expenditure. The research used secondary data from Badan Pemeriksa Keuangan Republik Indonesia Perwakilan Jawa Tengah based on Budget Realization Report, fiscal year from 2013-2015. Method of sample is saturated sample is all population is sample. The 105 data analized by linear regression analysis with SPSS 16 program. The result show local Revenue, General Allocatiom Fund and Spesial Allocation Fund have significant effect to servent expenditure, and Revenue Sharing Fund no significant effect to Servent Expenditure.